Critical thinking skills in English academic writing: An exploratory interview study of the perceptions and the experiences of EFL tutors at a Hungarian university - Kyi Phyu, Aye (Working Papers in Language Pedagogy, 2024)
The development of students’ critical thinking (CT) skills in English academic writing poses challenges for both educators and students within the realm of English language teaching. In response to these challenges, the present study examines two main research questions related to tutors' perceptions and their experiences in fostering CT skills in English academic writing classes at a Hungarian university. The study employed a qualitative exploratory approach and involved the participation of five EFL tutors. Data were collected through semi-structured interviews and analysed using thematic content analysis. The findings indicate that EFL tutors consider CT skills crucial for evaluating sources, analysing academic texts, questioning reliability, and expressing independent opinions. Various strategies are employed to foster CT skills, including sample texts, guided tasks, the process approach to teaching academic writing, technology use, written feedback, self-assessment, peer revision, and the Toulmin model. Challenges faced by EFL tutors include mixed English language proficiency levels of students, students' limited exposure to CT and academic writing, students' attitudes towards CT and academic writing, time constraints, and systemic issues. The study offers EFL tutors’ insights and effective strategies for enhancing students' CT skills in English academic writing.